Actin filaments altered distribution in wheat (Triticum aestivum) “Bending Root” to respond to enhanced Ultraviolet-B radiation - Du,M. T. (2021)
Abstract Plants adjust their shoot growth to acclimate to changing environmental factors, such as to enhanced Ultraviolet-B (UV-B) radiation. However, people have ignored that plant roots can also respond to UV-B light. Here, we find the morphology curled wheat roots under UV-B radiation, that we call, “bending roots.” The curly region is the transition zone of the root after observed at the cellular level. After exposed to enhanced UV-B radiation for 2 d (10.08 KJ/m2/d), cell size decreased and actin filaments gathered in wheat roots. We also find that H2O2 production increased and that content of the indole-3-acetic acid (IAA) increased remarkably. The pharmacological experiment revealed that actin filaments gathered and polymerized into bundles in the wheat root cells after irrigated H2O2 and IAA. These results indicated that actin filaments changed their distribution and formed the “bending root,” which was related to H2O2 production and increase in IAA. Overall, actin filaments in wheat root cells could be a subcellular target of UV-B radiation, and its disruption determines root morphology.